2023
DOI: 10.1182/bloodadvances.2022007082
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after biochemical or clinical progression in patients with multiple myeloma

Abstract: Almost all patients with multiple myeloma (MM) eventually relapse, either asymptomatically or with end-organ damage. However, it remains unclear if initiating therapy at the time of biochemical progression (BP) improves the outcomes, compared with therapy initiation at the clinical progression (CP) stage. Here, we retrospectively assessed 1347 relapsed MM patients. Most progressions were BP (60.4%); 39.6% had CP. The most prevalent symptoms at relapse were: new/evolving bone disease (80.9%), anemia (38.0%) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…A recent retrospective analysis of 1,347 patients demonstrated that MM patients who initiate new therapy at biochemical progression have a longer overall survival from relapse compared to those who initiate new therapy at clinical relapse. Therefore, sBCMA testing could utilize increases in patients’ sBCMA levels to indicate biochemical relapse in patients who develop nonsecretory disease, allowing for an earlier detection of disease progression resulting in improved clinical outcomes from being able to start a new line of therapy sooner [ 11 ]. Moreover, these patients and those with oligosecretory disease, where the monoclonal immune markers are detectable but below threshold levels (>1 g/dL for sMP and >100 mg/L for sFLC) [ 9 ], are ineligible for clinical trials because they are not considered evaluable.…”
Section: Discussionmentioning
confidence: 99%
“…A recent retrospective analysis of 1,347 patients demonstrated that MM patients who initiate new therapy at biochemical progression have a longer overall survival from relapse compared to those who initiate new therapy at clinical relapse. Therefore, sBCMA testing could utilize increases in patients’ sBCMA levels to indicate biochemical relapse in patients who develop nonsecretory disease, allowing for an earlier detection of disease progression resulting in improved clinical outcomes from being able to start a new line of therapy sooner [ 11 ]. Moreover, these patients and those with oligosecretory disease, where the monoclonal immune markers are detectable but below threshold levels (>1 g/dL for sMP and >100 mg/L for sFLC) [ 9 ], are ineligible for clinical trials because they are not considered evaluable.…”
Section: Discussionmentioning
confidence: 99%
“…Since its introduction, bortezomib has improved the survival and quality of life for patients with newly diagnosed MM. However, most patients eventually relapse [5]. Therefore, more effective therapies are highly needed.…”
Section: Introductionmentioning
confidence: 99%
“…CAR NK therapy utilizes "off-the-shelf" ready-to-use CAR NK cells that can be manufactured through mass production and infused to patients at any time. The second major advantage of using CAR NK cells over CAR T cells is that activation of CAR T cells can lead to massive release of inflammatory cytokines which can cause cytokine release syndrome (CRS) and neurotoxicity, whereas the activation of CAR NK cells releases inflammatory cytokines but does not cause CRS [5].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that early relapse within 12 or 24 months following initial therapy is associated with poorer survival outcomes for MM patients [5,[7][8][9]. Furthermore, it has been observed that MM patients experiencing clinical progression exhibit inferior post-progression outcomes compared to those with biochemical progression [10]. However, the real-world prevalence of time to progression (TTP) after achieving very good partial remission (VGPR) or complete remission (CR), as well as its clinical signi cance on MM patient outcomes, remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%